Combined effects of microencapsulated essential oils and γ-irradiation on microbiological and physicochemical properties of dry fermented sausages during ripening and storage. (March 2022) - Ji, Jiali; Shankar, Shiv; Salmieri, Stéphane; Lacroix, Monique
Abstract: The present study illustrates the effect of combined treatments of encapsulated essential oils (encapsulated in alginate or alginate-CNC) and γ-irradiation (at the dose of 1.5 kGy) on Escherichia coli O157:H7, Listeria monocytogenes, molds and yeasts, lactic acid bacteria (LAB), and total mesophilic bacteria (TMF), as well as pH, water activity, color, and texture in dry fermented sausages during ripening and vacuum packed during storage at room temperature (20–21 °C) for 20 weeks. Combined treatments showed synergetic effects on inhibiting resistant Escherichia coli O157:H7 cocktail isolated from dry fermented sausage responsible of an E. coli outbreak and LAB. Results also showed a strong inhibition of Listeria monocytogenes, molds and yeasts, and TMF. Furthermore, the combined treatments did not affect the texture of the sausages and encapsulation of the essential oils contributed to the color protection of the sausages. Highlights: Microencapsulation (ME) of essential oils (EOs) in alginate or alginate-CNC. EOs, ME and γ-irradiation (GI) showed synergetic antimicrobial effects. EOs, ME or GI did not affect the texture of dry fermented sausages (DFS). Colors of DFS treated with EOs, ME and GI were more stable during storage.